2005
DOI: 10.1177/070674370505001007
|View full text |Cite
|
Sign up to set email alerts
|

Service Use for Mental Health Reasons: Cross-Provincial Differences in Rates, Determinants, and Equity of Access

Abstract: Objectives: In 2002, Canada undertook its first national survey on mental health and well-being, including detailed questioning on service use. Mental disorders may affect more than 1 person in 5, according to past regional and less comprehensive mental health surveys in Canada, and most do not seek help. Individual determinants play a role in health resource use for mental health (MH) reasons. This study aimed to provide prevalence rates of health care service use for MH reasons by province and according to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
111
3
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(125 citation statements)
references
References 32 publications
7
111
3
4
Order By: Relevance
“…35 Furthermore, a Canadian study that examined barriers to mental health care using data from the Canadian Community Health Survey concluded that "despite universal health insurance, there are significant inequi ties in access to mental health care for low-income Canadians." 36 been shown to exist 35,37 and results from our study might well reflect real regional differences. However, given the many nested factors that may contribute to our observations, we refrain from drawing any specific inferences from these findings.…”
Section: Discussionsupporting
confidence: 58%
“…35 Furthermore, a Canadian study that examined barriers to mental health care using data from the Canadian Community Health Survey concluded that "despite universal health insurance, there are significant inequi ties in access to mental health care for low-income Canadians." 36 been shown to exist 35,37 and results from our study might well reflect real regional differences. However, given the many nested factors that may contribute to our observations, we refrain from drawing any specific inferences from these findings.…”
Section: Discussionsupporting
confidence: 58%
“…On sait qu'il existe des différences dans l'utilisation des services de santé mentale d'une province à l'autre 35,37 , et les résultats de notre étude pourraient donc refléter de réelles différences régionales. Toutefois, étant donné les nombreux facteurs sous jacents susceptibles d'avoir pu contribuer à ces observations, nous préférons nous abs tenir d'en tirer des conclusions précises.…”
Section: Raisons Invoquées Pour Ne Pas Avoir Eu Recours Aux Médicamenunclassified
“…Young (2001) rapporte que seulement 19 % des personnes qui ont consulté des services de première ligne ont reçu des soins adé-quats, contre 90 % qui ont consulté un spécialiste en santé mentale. Or, les médecins généralistes sont les plus consultés par les personnes souffrant de troubles anxieux (Vasiliadis et al, 2005 ;Wang et al, 2005) ; puisque ces dernières consultent davantage les services de soins primaires, il importe dès lors d'améliorer l'arrimage entre les différents services. C'est d'ailleurs un des objectifs du Plan d'action en santé mentale du Québec où l'on favorise le traitement des troubles modérés de santé mentale en première ligne, visant ainsi une évaluation et un traitement rapide, tant au plan médical que psychosocial (MSSS, 2005).…”
Section: Les Difficultés D'accès Au Traitementunclassified
“…Ces dernières ont en effet tendance à consulter peu ou à attendre très longtemps avant de le faire, en raison des comportements d'évitement présents chez elles. De tous les troubles transitoires modérés de santé mentale, ces problèmes ont d'ailleurs les taux de consultation les plus bas (Kessler et al, 1999 ;Vasiliadis et al, 2005 ;Wang et al, 2005). Il importe donc d'améliorer l'accès au traitement pour ces personnes (Olfson et al, 1998 ;Perreault et al, 2004).…”
unclassified